Impactos do uso público EM atrativos turísticos naturais no município de AltinóPolis (SP) - Sardinha, Diego de Souza [UNESP]; Da Conceição, Fabiano Tomazini [UNESP]; Carvalho, David Ferreira; Cunha, Rafael; De Souza, Antonio Donizetti Gonçalves (My University, 2007)
This work was developed aiming to evaluate the environmental impacts of the public use in natural touristic attractive at Altinópolis city (SP), using the Visitor Impact Management method (VTM). In each analyzed natural resource a specific questionnaire was elaborated in accordance with the appropriate pointers that allowed to determinate environmental quality of each point. The results indicated that only two tourist areas need special attention for their preservation. Minimization methods, monitoring and educational practices are proposals in order to tourist practices be made with environmental responsibility.

Este trabalho foi desenvolvido com a intenção de avaliar os impactos ambientais do uso público em atrativos turísticos naturais no Município de Altinópolis (SP), sendo utilizado para isso o método Visitor Impact Management (VIM). Em cada recurso natural analisado foi elaborado um questionário específico de acordo com os indicadores apropriados que permitiram determinar a qualidade ambiental de cada ponto. Os resultados indicaram que apenas duas áreas turísticas necessitam de uma atenção especial para a sua conservação. Métodos de minimização, monitoramento e práticas educacionais são propostas para que essas atividades turísticas sejam realizadas com responsabilidade ambiental. Palavras-chave: Práticas turísticas, método VIM, Altinópolis, sustentabilidade.
Impacts of the public use in natural tourist attractives at Altinópolis Municipality (SP)
Keywords: Altinópolis; Sustainability; Tourist practices; Visitor impact management; environmental impact assessment; monitoring; natural resource; public access; questionnaire survey; sustainability; tourism; tourist destination; Altinopolis; Brazil; Sao Paulo [Brazil]; South America